Characterization of 12S rRNA Gene for Species Identification of Common Indian Wild and Domestic Birds - Oad, Amit; Shrivastav, Awadh B; Jadav, Kajal; Rajput, Nidhi; Rokde, Amol; Govil, Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Poaching is a major threat to birds, mammals, plants and reptiles. The Indian peafowl (Pavo cristatus), a ‘gallinaceous bird’, is the national bird of India and belongs to Schedule I of the Indian Wildlife (Protection) Act, 1972. The bird is often killed for its tail feathers and meat. For the effective implementation of law and order, firm evidences are required against the poachers. Additionally, phylogenetic analysis is required to study the biodiversity of avian fauna for better understanding of genetic evolution. Hence, in the present study, characterization of 12S rRNA gene was performed for genomic analysis and phylogentic relationship of Indian peafowl with other free-ranging and domestic birds. A total of 54 Forensically Informative Nucleotide Sequences (FINS) were identified in the present study for identification of species of the panel birds. The phylogenetic analysis was inferred using the Neighbor-joining tree in which different wild bird species were found to be restricted to different clades. Data obtained in the present study using partial fragment of 12S rRNA gene for tissue and faecal samples might be a useful and convenient tool for species identification and can be readily applied to other bird assemblages, making them particularly relevant to a broad range of further avian research.
Keywords: Birds; FINS; Forensic; Phylogeny; Wildlife